Monks: A Population at Risk for Liver Fluke and Skin-Penetrating Helminths - Nuttapon Ekobol; Sirintip Boonjaraspinyo; Atchara Artchayasawat; Thidarut Boonmars (Tropical Medicine and Infectious Disease, 2023)
Monks cannot cook received raw meat dishes and should walk barefoot while working. This population lacks both a survey of parasitic infection and a proper prevention and control policy. Five hundred and fourteen monks from the Ubolratana, Ban Haet, and Ban Phai Districts of Kh on Kaen Province were enrolled in this study. A stool container and questionnaire were collected from each study participant. Stool samples were processed by formalin ethyl acetate concentration and agar plate culture techniques. We then analyzed the results and risk factors to demonstrate associations. The prevalence of overall parasites, liver flukes, and skin-penetrating helminths were 28.8%, 11.1%, and 19.3%, respectively. Raw fish dish offerings were associated with opisthorchiasis (ORcrude 3.32; 95% CI 1.53–7.20). The risk factors for skin-penetrating helminths were older age (ORcrude 5.02; 95% CI 2.2–11.17), being a long-term ordinate (ORcrude 3.28; 95% CI 1.15–9.34), smoking (ORcrude 2.03; 95% CI 1.23–3.36), and chronic kidney disease with other underlying disease (ORcrude 20.7; 95% CI 2.54–190.1). The protective factors for skin-penetrating helminths were secular education above primary education (ORcrude 0.41; 95% CI 0.25–0.65) and having received health education about parasitic infection (ORcrude 0.47; 95% CI 0.28–0.80). Wearing shoes at times other than alms work does not show a protective effect against skin-penetrating helminths (ORcrude 0.86; 95% CI 0.51–1.46). These findings support the recommendation for a strict Rule of Discipline regarding raw meat ingestion and allowing shoes to be worn for protection against skin-penetrating helminths in high-risk situations.